2014
DOI: 10.1016/j.fuel.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Partial briquetting vs direct addition of biomass in coking blends

Abstract: In this work partial briquetting is employed as a means of biomass densification to allow for biomass inclusion in coking coal blends. The effect of increasing the bulk density was evaluated by comparison with direct addition. Two briquettes of different composition were studied. The influence of the briquettes on the Gieseler plasticity of the coals was determined. It was found that the effect of the binder was not enough to compensate for the decrease in plasticity produced by the inert components of the bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 23 publications
1
32
1
Order By: Relevance
“…In a previous research paper it was shown that the direct addition of sawdust to an industrial coal blend produced a decrease in the bulk density of the charge of 17 kg/m 3 while the addition of sawdust in the form of briquettes increased it by 11 kg/m 3 [7].…”
Section: Characteristics Of the Materialsmentioning
confidence: 96%
See 2 more Smart Citations
“…In a previous research paper it was shown that the direct addition of sawdust to an industrial coal blend produced a decrease in the bulk density of the charge of 17 kg/m 3 while the addition of sawdust in the form of briquettes increased it by 11 kg/m 3 [7].…”
Section: Characteristics Of the Materialsmentioning
confidence: 96%
“…At the same time, cokemaking is a process where the recycling of wastes is possible, especially high carbon and low ash wastes like sawdust and charcoal [5][6][7][8][9], plastics [10][11][12], and bituminous wastes [13][14][15]. Thus recycling in the cokemaking industry could provide a way to reduce the environmental impact of CO 2 emissions, reduce costs and widen the raw materials spectrum to include non-fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The briquettes had an ellipsoidal shape, axes of lengths 46 and 42 mm and a weight of around 23 g (Montiano et al, 2014b). Blends resembling the composition of the briquettes were pyrolyzed up to 1000 °C at a rate of 10 °C/min in order to investigate the degree of interaction between the components of the blends.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…In addition the recycling of wastes is important not only from the point of view of waste treatment and energy recovery but also for upgrading the material. The use of biomass in coking blends could serve to reduce the emission levels due to its carbon neutral content and low ash and sulphur contents (Jung et al, 2014;Montiano et al, 2014aMontiano et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%